2015
DOI: 10.1002/ente.201500067
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High‐Performance Supercapacitors by Constructing Porous Zinc–Manganese Oxide Microstructures

Abstract: Porous zinc-manganese oxide (ZnMn 2 O 4 )m icrostructures are prepared by calcination using ap recursorm ethod, and the material is successfully applied as the supercapacitor electroactive materials in at hree-electrode cell. Due to the uniquem icro/nanostructure,t he as-prepared sample obtained under the calcinationc onditiono f4 50 8Cf or 6h achieved ah igh specific capacitance of 1093 Fg À1.T he electrode also exhibited high cycle stability for 5000 cycles.In recent years,porousm aterials have been widelya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…ZnMn 2 O 4 is an interesting compound that has been widely used as an electrode for Li-ion batteries due to its low cost and being environmentally friendly [19,20,21,22,23,24]. Also, this material has been used as a supercapacitor [25,26,27,28,29] and thermistor [30] due to its structural, physical, and chemical properties. It has been reported that zinc manganite shows strong catalytic activity [31,32,33,34,35]; therefore, this material could perform well as a gas sensor.…”
Section: Introductionmentioning
confidence: 99%
“…ZnMn 2 O 4 is an interesting compound that has been widely used as an electrode for Li-ion batteries due to its low cost and being environmentally friendly [19,20,21,22,23,24]. Also, this material has been used as a supercapacitor [25,26,27,28,29] and thermistor [30] due to its structural, physical, and chemical properties. It has been reported that zinc manganite shows strong catalytic activity [31,32,33,34,35]; therefore, this material could perform well as a gas sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, ternary transition metal oxides have shown better performance than single metal oxides due to their possible synergetic enhancement . Hence, nanostructured ZnMn 2 O 4 has been investigated to improve the electrochemical performance for LIBs …”
Section: Introductionmentioning
confidence: 99%
“…[10] Hence,n anostructured ZnMn 2 O 4 has been investigatedtoimprovet he electrochemical performancefor LIBs. [10][11][12][13][14][15][16][17][18][19][20][21][22] Nanosheets and nanofibers are important in various applications such as optoelectronics, [23] solar cells, [24] and LIBs, [25] because of their high specific surface areas and short transport paths for electrons and ions.I np articular, such nanostructured materials have been extensivelys tudied as alternative LIB electrodes,with long-term cycling and ahighly reversible electrode reaction as ar esult of their ability to buffer the mechanical stress more effectively during repeated cycling.T os ynthesize the nanostructure,v ariousm ethods have been explored, mostly including hydrothermal or template routes. [26,27] However, these methods are often involved with complexp rocesses.E lectrospinning is as imple and effective methodf or fabricating nanostructures,a nd this methoda long with particular thermal treatment could be used to achieve many interestingm ultilevel nanostructures (branched nanowires, [24] wire-in-tube, [28] bamboo joint [29] ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the other designs [21,57], it is significant to put forward the idea of novel sandwich-like ZnMn 2 O 4 nanoparticles encapsulated in carbon nanosheets (sandwichlike ZnMn 2 O 4 /C). In this study, the massive sandwiched ZnMn 2 O 4 /C was prepared through a simple hydrothermal and sacrificial template method.…”
Section: Introductionmentioning
confidence: 99%